Crystallinity control of TiO2 hollow shells through resin-protected calcination for enhanced photocatalytic activity. Issue 1 (16th October 2014) - Liu, Hongyan; Joo, Ji Bong; Dahl, Michael; Fu, Lishun; Zeng, Zhengzhi; Yin, Yadong
Abstract : A resin overcoat allows effective control over the crystallization of hollow titania nanoshells during calcination and enhances their photocatalytic activity. Abstract : We report a novel resin-protected calcination process for preparing hollow TiO2 nanoshells with controllable crystallinity and phase. This method involves coating a template core with TiO2 and then a protection layer through sol–gel processes and then crystallization of the TiO2 shell by calcination. Through a systematic study on the crystallization behaviour of the TiO2 hollow shells with variation in core template and outer protection layer, we find that the grain growth and phase transformation of TiO2 is determined by several parameters such as the protection material, core composition, and calcination conditions. In particular, the use of a crosslinked polymer as the protection layer for calcination, enables the production of TiO2 shells with high crystallinity and controllable anatase–rutile mixed phases, which show significantly enhanced photocatalytic activity compared to those produced by SiO2 -protected calcination. The photocatalytic activity could be further improved by improving the water dispersity of TiO2 shells through base treatment. With the ease of achieving photocatalytic activity comparable to commercial Degussa-P25 TiO2, it is expected that the TiO2 shells with controllable crystallinity and phase could be further engineered by incorporating more active components for producing highly active composite photocatalysts.